Students’ Difficulties in doing Listening Section of TOEFL Test - Oktody Herdianto (Teaching English and Language Learning English Journal, 2022)
This research objectives are to investigate the students’ difficulties in doing listening section of TOEFL Test and to investigate the most dominant students’ difficulties in listening section of TOEFL Test The design of this research was a descriptive quantitative research, because in this research, the researcher described the students’ difficulties of listening section on TOEFL Test at sixth semester English education program. Subject of the research was the whole students of the sixth semester of English Language Education Study Program of UMB Bengkulu Academic Year 2021/2022. There were 20 students as the sample of this research. The instruments of this research were questionnaire and interview. Questionairre is a list of question that describe of something. The questionnaire was designed based on Fitria (2021) theory who divided the students difficulties into; internal factors and external factors. There are two findings of this research; First, the students’ difficulties in listening section of TOEFL Test in University of Muhammadiyah Bengkulu are including internal factors and external factors. Second, the most dominant students’ difficulties in listening section of TOEFL Test in University of Muhammadiyah Bengkulu was external factor. The dominant external factors were speakers’ intonation/emphasis affects your TOEFL Listening skill, the sentence structure conveyed by the speaker is too complex so it affects the TOEFL Listening skill, and audio interruption makes the audio sounds less/unclear when Listening TOEFL. Keywords : Difficulties in doing Listening Section, TOEFL Test